Impact of technological innovations on the investment behaviour of stock market investors - Aghilesh, M. (Govt. College Madapally, University of Calicut, 2025)
he technology used for stock trading continues to develop rapidly, which has asignificant impact on stock market participation, particularly in developing economieslike India. The current study, titled “Impact of Technological Innovations on theInvestment Behaviour of Stock Market Investors”, explores the effects oftechnological innovations on the investment behaviour of retail investors. The studyis both analytical and empirical in nature, relying on primary and secondary data. Astructured questionnaire was used to collect primary data from 420 active stock marketinvestors in Kerala, who were selected purposively. Descriptive statistics, Mann-Whitney U Test, Kruskal-Wallis H Test, and Partial Least Squares Structural EquationModelling (PLS-SEM) were used in the analysis. The results indicate that the attitudeof investors towards technological innovations is the most important variabledetermining their use of fintech tools. The attitude had a significant positive impacton the probability of investors intending to utilise such tools, and risk and costconcerns decreased after the adoption decision. These findings provide empiricalevidence to support the existing theories of technology adoption, demonstrating theirapplicability in financial contexts. The research also indicates that technologicalchanges transform investor behaviour to be more dynamic, enlightened and active intrading. In the context of practicality, the implications of the results to brokerage firms,regulators and policymakers are considerable. Brokerage firms are encouraged todevelop user-friendly platforms that incorporate onboarding tracks tailored to variousinvestor segments, video tutorials, and regional language support to enhanceaccessibility. Such insights can be utilised by regulators and policymakers to designpolicies that promote the responsible use of financial technologies, striking a balancebetween innovation and investor protection. The study contributes to the theoreticaldiscussion of technology adoption. It lays the groundwork for future research infinancial markets, particularly in the investigation of the ever-changing fintechsolutions and their long-term effects on retail investment behaviour.
Keywords: Technological Innovations; Investment Behaviour; Stock Market Investors; Discount Brokers; Stock Screeners.